Perspective-taking influences attentional deployment towards facial expressions of pain: an eye-tracking study. Issue 6 (June 2020) - Pilch, Monika; O'Hora, Denis; Jennings, Caroline; Caes, Line; McGuire, Brian E.; Kainz, Veronika; Vervoort, Tine
Abstract : Abstract: Empathetic perspective-taking (PT) may be critical in modulating attention and associated responses to another's pain. However, the differential effects of imagining oneself to be in the pain sufferer's situation ("Self-perspective") or imagining the negative impacts on the pain sufferer's experience ("Other-perspective") on attention have not been studied. The effects of observer PT (Self vs Other) and level of facial pain expressiveness (FPE) upon attention to another person's pain was investigated. Fifty-two adults were assigned to 1 of 3 PT conditions; they were instructed to view pairs of pain expressions and neutral faces and either (1) consider their own feelings (Self-perspective), (2) consider the feelings of the person in the picture (Other-perspective), or (3) received no further instructions (Control). Eye movements provided indices of early (probability and duration of first fixation) and later (total gaze duration) attentional deployment. Pain faces were more likely to be fixated upon first. A significant first fixation duration bias towards pain was observed, which increased with increasing levels of FPE, and was higher in the Self-PT than the Control condition. The proportion of total gaze duration on pain faces was higher in both experimental conditions than the Control condition. This effect was moderated by FPE in the Self-PT condition; there was a significant increase from low to high FPE. When observers attend to another's facial display of pain, top-down influences (such as PT) and bottom-up influences (such as sufferer's FPE) interact to control deployment and maintenance of attention. Abstract : Supplemental Digital Content is Available in the Text.Top-down (perspective-taking) and bottom-up (facial pain expressiveness) characteristics, as well as the interaction between the 2, affect attention to pain in others.